Valuation of Ecological Services in the RideauValley Watershed - Handa, Nina (Université d'Ottawa | University of Ottawa, 2010)
Watershed provide humans with many ecological goods and services such as clean water, erosion control, carbon sequestration and biodiversity that are not valued by the markets. The valuation of ecological benefits economically is a challenge for the formu